PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PT ASURANSI KREDIT INDONESIA - Budi Santoso Ali; Iwan Kurniawan Subagja; Muhammad Harri (Jurnal Manajemen Bisnis Krisnadwipayana, 2025)
This study aims to determine influence of leadership style and organizational culture affect employee performance through job satisfaction as an intervening variable. This study uses primary and secondary data by distributing questionnaires to employees of PT Asuransi Kredit Indonesia. The population in this study is employees of PT Asuransi Kredit Indonesia. Data analysis method using path analysis. The results of the study show that 1) Leadership style has a positive and significant effect on employee performance. 2) Organizational culture has a positive and significant effect on employee performance. 3) Leadership style has a positive and significant effect on job satisfaction. 4) Organizational culture has a positive and significant effect on job satisfaction. 5) Job satisfaction has a positive and significant effect on employee performance. 6) job satisfaction cannot mediate leadership style in influencing employee performance. 7) Job satisfaction cannot mediate organizational culture in influencing employee performance.